(6x+4)(x-7)=0

Simple and best practice solution for (6x+4)(x-7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+4)(x-7)=0 equation:



(6x+4)(x-7)=0
We multiply parentheses ..
(+6x^2-42x+4x-28)=0
We get rid of parentheses
6x^2-42x+4x-28=0
We add all the numbers together, and all the variables
6x^2-38x-28=0
a = 6; b = -38; c = -28;
Δ = b2-4ac
Δ = -382-4·6·(-28)
Δ = 2116
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{2116}=46$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-38)-46}{2*6}=\frac{-8}{12} =-2/3 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-38)+46}{2*6}=\frac{84}{12} =7 $

See similar equations:

| 6x+4=10+4x-8 | | m(-1)/3=2m-7 | | 1+3c=c+7 | | p-3=2p+4 | | -8-10y=-2y | | 3x+9-8x+6=62/3 | | -159+13x=45+7x | | 4x^2+8x-896=0 | | -z+10=4z | | 96=(3x+5)x | | -1=-2/3x+5 | | 0.4(x+5)=0.2(10-12x)+x | | 6-8b=-9b | | Y=216-2x | | 7+v-3=6=v | | 4(t+9)=4(t+9) | | 2x^2+8x=896 | | 81=10y | | 6w+5w-22=77 | | −13+2z=−56 | | 4n+26+4n=180 | | 3m+1=2m+3-1 | | -11x-56=-14x+19 | | 2x+5=10x+13 | | 9.6-0.7x=5.4 | | 9.16=2d | | -29+9x=46+4x | | 10x^2×18x-616=0 | | 12.9x+10=34 | | 2(a+3)=5-3(a-2) | | 5.6m-7.4=32.92 | | 9h-6+12+40=22 |

Equations solver categories